Relacje pomiędzy aktywnością enzymatyczną a właściwościami gleb i sposobem użytkowania - Błońska, Ewa; Lasota, Jarosław; Zwydak, Maciej (Leśne Prace Badawcze, 2017)
The aim of this study was to assess the effects of different types of land use (forest, tillage and pasture) on soil properties, especially enzymes activity. Our investigation was carried out on 53 research plots with 11 plots in broadleaved forest stands, 12 plots in mixed broadleaved stands, 10 plots in mixed coniferous stands, 9 plots on tillage and 11 plots on pasture. The soil samples were collected from a depth of 0–15 cm after removing the organic horizon. Contents of organic carbon and nitrogen, pH and soil texture were investigated. Furthermore, dehydrogenase and urease activity were determined. Significant differences in the enzyme activity between forest and agricultural soils were observed, thus demonstrating that enzyme activity is influenced by the organic matter content of the soil. The highest enzyme activity was recorded in the forest soil within broadleaved stands, whilst the lowest activity was found in tillage soil, because tillage soil contained significantly less organic matter. High enzymatic activity of pasture soils is the combined result of vegetation type and the lack of plowing.